2020
DOI: 10.1021/acsanm.0c00748
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica-Capped Silver Nanoparticles for Sieving and Surface-Enhanced Raman Scattering-Based Sensing

Abstract: Surface-enhanced Raman scattering (SERS) is observed solitarily for analytes that are placed in the vicinity of plasmonic nanoparticles since the amplitude of the electric field on their surface decays with distance. Taking this idea forward, we have designed core−shell plasmonic systems for SERS sensing, consisting of silver nanoparticles coated with mesoporous silica (Ag@m-SiO 2 ) having an average pore size of 2.4 nm. Studies presented herein show that a Ag nanoparticle core of ∼55 nm and an m-SiO 2 shell o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…Silver nanoparticles with a size of ∼50 ± 3 nm are prepared using the Turkevich method and coated with poly­(vinylpyrrolidone) (PVP) to make the surface vitreophilic and to facilitate silica coating. The Stöber method of coating is adopted to achieve silica coating around the silver nanoparticles, and the advantages of using silica as a capping agent for plasmonic nanoparticles are as follows: (i) high stability, (ii) chemical inertness, (iii) optical transparency, (iv) tunability in thickness, (v) controllable porosity, and (vi) the possibility of surface modification. , Similarly, gold nanoparticles are synthesized by seed-mediated synthesis and are coated with PVP for stabilization. These particles are then coated with SiO 2 having a thickness t ∼ 3 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Silver nanoparticles with a size of ∼50 ± 3 nm are prepared using the Turkevich method and coated with poly­(vinylpyrrolidone) (PVP) to make the surface vitreophilic and to facilitate silica coating. The Stöber method of coating is adopted to achieve silica coating around the silver nanoparticles, and the advantages of using silica as a capping agent for plasmonic nanoparticles are as follows: (i) high stability, (ii) chemical inertness, (iii) optical transparency, (iv) tunability in thickness, (v) controllable porosity, and (vi) the possibility of surface modification. , Similarly, gold nanoparticles are synthesized by seed-mediated synthesis and are coated with PVP for stabilization. These particles are then coated with SiO 2 having a thickness t ∼ 3 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[39] It has been reported that a comprehensive method for silver nanoparticles coated with mesoporous silica with core-shell plasmonic systems for SERS detecting (Figure 2). [40] Ag-MSNs with core-shell structure had an obvious SERS phenomenon. So far, more studies have been carried out drug delivery for tumor therapy, SERS imaging and tumor photothermal therapy.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…(D)The fabrication procedure for the Ag-MSNs@CHX and application for SERS imaging and pH-sensitive drug delivery in cancer therapy. Reconstructed with permission from [29,40,42].…”
mentioning
confidence: 99%
“…They could be generally divided into metal-based, metal oxides-based, and carbon-based NPs. Metal-based NPs (MNPs), especially the noble metals, have drawn more attention because of their optical, electrical, and sensing characteristics [18][19][20][21] . MNPs could be synthesized via several pathways such as electrochemical techniques, laser ablation, γ-radiation, photochemical techniques, and chemical reduction 22 .…”
Section: Introductionmentioning
confidence: 99%